Experimental analysis on 3D printing of dissimilar metal materials - Tan, Wei Jie (Nanyang Technological University, 2023)
Additive Manufacturing (AM) is a rapidly developing technology that will revolutionize the manufacturing industry. Despite its wide range of industrial applications and manufacturing capabilities, there are still inadequate literature on the AM of dissimilar metal materials. Therefore, the primary goal of this study is to understand and identify the optimal print parameters to achieve the best the mechanical properties, microhardness and strength of the dissimilar metal materials using Selective Laser Melting (SLM). The print parameters studied include laser power, scanning speed, hatch distance, point distance, powder layer thickness, and exposure time to the laser. This is achieved through conducting experimental analysis in the form of material microhardness analysis and material tensile stress analysis on the printed CoCrMo powder to CuZrCr substrate. The microhardness and ultimate tensile strength of the AM dissimilar metal part highlights the quality of the part produced. This article identifies and discusses the limitations of the thermal mismatch of metals due to the different coefficient of thermal expansion and how the different printing parameters can help to reduce the significance of such limitation to produce a part with an improved interface. The experimental analysis identified that remelting the first print layer three times will improve the microhardness of the printed part. A fracture at the substrate during tensile strength analysis is also an indicator that the print parameters reduced the thermal mismatch of the AM part, improving the ultimate tensile strength. Through understanding of how the interface of dissimilar metal materials is affected by the different print parameters, future studies can utilize this important information to create better multi material parts from AM.